Managing Islamic Academic Libraries in Indonesia in the Era of Society 5.0 and Artificial Intelligence: Readiness and Challenges Analysis - Rodin, Rhoni (Khizanah al-Hikmah : Jurnal Ilmu Perpustakaan, Informasi, dan Kearsipan, 2025)
This study analyzes the readiness and challenges encountered by Islamic academic libraries in Indonesia in adapting to AI-driven digital transformation. Employing a literature review approach, the research synthesizes findings from academic studies, institutional reports, and related literature to examine four central aspects: technological readiness, focusing on the adoption of AI and automation in library operations; human resource readiness, assessing librarians’ competencies in managing digital systems; implementation challenges, identifying obstacles such as limited infrastructure, financial constraints, and digital literacy deficits; and development strategies, offering recommendations to enhance digital library services while upholding Islamic educational values. The findings revealed that while several Islamic academic libraries have initiated steps toward digitalization, persistent barriers hinder comprehensive implementation. Notably, disparities in infrastructure and professional capacity highlight the urgent need for strategic action. The study concludes that successful digital transformation requires sustained investment in technology, ongoing professional development for librarians, and inter-institutional collaboration. Strengthening these areas will enable Islamic academic libraries to evolve into dynamic digital knowledge hubs that contribute meaningfully to academic advancement in the Society 5.0 era.